1995
DOI: 10.1029/95ja00655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local interstellar medium hydrogen fractional ionization on the distant solar wind and interface region

Abstract: The paper investigates the influence of the local interstellar medium (LISM) proton number density on the gasdynamics of LISM / solar wind interaction. It uses the self‐consistent axisymmetric model of Baranov and Malama (1993) for a constant value of the LISM neutral hydrogen number density (nH∞ = 0.14 cm−3). It is shown that the flow structure is asymmetric relative to the upwind and downwind directions. Numerical results are presented for four values of the proton number density in the LISM: np∞ = 0.005; 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 11 publications
2
59
0
Order By: Relevance
“…Secondary interstellar atoms, which are a result of charge exchange of the original interstellar H atoms and solar wind protons, disturb the interstellar gas upwind the bow shock. Detail studies of mutual influences of charge and neutral components in the heliospheric interface were done in Baranov and Malama (1993,1995, 1996, Baranov et al (1998), Izmodenov et al (1999Izmodenov et al ( , 2000Izmodenov et al ( , 2001. However, these papers were mainly focused on the upwind region.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary interstellar atoms, which are a result of charge exchange of the original interstellar H atoms and solar wind protons, disturb the interstellar gas upwind the bow shock. Detail studies of mutual influences of charge and neutral components in the heliospheric interface were done in Baranov and Malama (1993,1995, 1996, Baranov et al (1998), Izmodenov et al (1999Izmodenov et al ( , 2000Izmodenov et al ( , 2001. However, these papers were mainly focused on the upwind region.…”
Section: Introductionmentioning
confidence: 99%
“…a background magnetic field B LISM exists which is oriented parallel to the stagnation line (i.e., according to an MHD interaction model with B LISM V LISM as treated, e.g., by Baranov & Malama 1995;Pogorelov & Matsuda 1998;or Ratkiewicz & McKenzie 2003), one then can assume that Alfvén waves are excited by this free energy which then propagate upstream and downstream of the plasma flow. The free energy of newly injected protons stemming from the bulk of the H-atom distribution function can then be assumed to be pumped into the wave field at the injection wave number fulfilling the resonance conditions and given in the bulk plasma system by:…”
Section: Outlook: Competing Proton Relaxation Processes In Heliosphermentioning
confidence: 99%
“…The Lyman-α diagnostic for stellar mass loss rates Baranov & Malama (1995) showed that charge exchange processes between solar wind protons and neutral hydrogen atoms in the local interstellar medium (ISM) produce a population of heated, decelerated hydrogen atoms concentrated in the interstellar upwind direction, the so-called "hydrogen wall". These calculations and those in subsequent models of Zank et al (1996), Izmodenov et al (1999), and Müller et al (2001) allowed Wood et al (2001) to computeṀ for α Cen.…”
Section: Why Mass Loss Rates Are Needed For the Sun And Cool Dwarf Starsmentioning
confidence: 99%